Psychometric evaluation of the body understanding measure pregnancy scale Chinese version for pregnant Chinese women. (September 2022) - Wu, Yinyin; Dai, Jiamiao; Chen, Xiangxu; Xie, Tianqu; Han, Lu; Wu, Yuanyuan; Chen, Yongfeng; Liu, Yanqun; Cai, Zhongxiang; Zhang, Wenhui; Bai, Jinbing
Abstract: Objectives: At present, there is limited research on pregnancy body image and no valid tool to measure body image in pregnant Chinese women. The purpose of this study was to translate the Body Understanding Measure Pregnancy Scale into Chinese to determine its reliability and validity in measuring body image in pregnant women. Methods: The translation of the Body Understanding Measure Pregnancy Scale (BUMPs) was carried out with a standardized procedure. This study was conducted from July to December 2020 in the outpatient department of three tertiary hospitals in China. There were 1069 pregnant women completed the questionnaire and 1057 of those women were included in the analysis. Internal consistency, test-retest reliability, content validity, and construct validity of the translation version were examined. Results: The final Chinese version of the BUMPs (BUMPs-C) had four dimensions with 16 items. Exploratory factor analysis obtained a three-factor solution, which explained 50.26% of the total variances. Confirmatory factor analysis showed that the model fit of the four-factor model was better than the three-factor model, and the four-factor model also reached a satisfactory model fit after modifying: Minimum Discrepancy was 2.82; Comparative Fit Index was 0.939, and Tucker-Lewis Index was 0.92; Root Mean Square Error of Approximation was 0.059. The content validity index of the scale was 1.0; the Cronbach's alpha (α) coefficient was 0.82 for the total scale, the McDonald's omega (ω) coefficient was 0.829; the test-retest reliability was 0.796. Conclusions: The BUMPs-C showed good reliability and validity among pregnant Chinese women, which can be used as a simple and valid measurement tool to assess the feelings of pregnant Chinese women on body changes during pregnancy.